2019
DOI: 10.3390/ijerph16050794
|View full text |Cite
|
Sign up to set email alerts
|

Is Repeat Abortion a Public Health Problem among Chinese Adolescents? A Cross-Sectional Survey in 30 Provinces

Abstract: The Chinese Family Planning (FP) programme mainly focuses on married couples, and young unmarried women have limited access. This cross-sectional study aims to identify risk factors related to repeat abortions in Chinese adolescents receiving abortions. Data were collected using a questionnaire for all women seeking abortions within 12 weeks of pregnancy during a period of 2 months in 297 participating hospitals randomly selected across 30 provinces of China in 2013. Only the adolescents (younger than the mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…Hospitals were then randomly selected from six independent sampling frames. One to three more hospitals were intentionally selected for Level 1 and Level 2 hospitals (depending on the size of the original pool of hospitals), to account for potential refusals and/or unforeseen challenges in implementing data collection 15 . The final sample included 297 hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…Hospitals were then randomly selected from six independent sampling frames. One to three more hospitals were intentionally selected for Level 1 and Level 2 hospitals (depending on the size of the original pool of hospitals), to account for potential refusals and/or unforeseen challenges in implementing data collection 15 . The final sample included 297 hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…The overall prevalence of repeat induced abortion in Chinese women was 43.1%, which is much higher than that of female abortion seekers elsewhere in the world: UK (19.2%$26.8%) [7,12,13], Switzerland (30.1%) [14], Norway (36.7%) [15], Netherlands (36.0%) [17], Ethiopia (20.3%$34.9%) [18][19][20], Canada (31.8%) [21] and Tunisia (42.2%) [22]. No direct evidence has been found about why Chinese women have a higher prevalence of repeat induced abortion; however, this difference might be relevant to the gap in sexual education and contraceptive practice in China compared with other, particularly developed, countries [39]. Furthermore, the study identified an increase in the prevalence of repeat induced abortion among Chinese women from 39.9% between 2007 and 2014 to 46.6% between 2015 and 2019, which might have been affected by China's two-child policy [26].…”
Section: Findings and Interpretationmentioning
confidence: 99%
“…There were multiple factors associated with repeat induced abortion. Firstly, social characteristics, such as age, education, migrants, parity, occupation, marriage, and fertility status showed a relation to repeat induced abortion [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]; secondly, personal behavior factors such as tobacco use, sexual debut, and number of sexual partners were also shown to be relevant [ 20 , 21 , 22 , 23 , 24 , 25 ]; thirdly, women who had experienced intimate partner violence or a family breakdown during childhood are at greater risk of repeat induced abortions [ 22 , 24 , 26 , 27 ]; finally, the practice of contraception and failure to use or incorrect use of contraceptives has increased the risk of repeat induced abortions [ 13 , 14 , 18 , 19 , 20 , 28 ]. Most of the studies used logistic regression to determine the characteristics of women with repeat induced abortions.…”
Section: Introductionmentioning
confidence: 99%